KONTEMPLASI DIANTARA MITOS DAN REALITAS (CONTEMPLATION BETWEEN MYTHS AND REALITIES) - I Wayan Kariarta (Jnanasidanta, 2019)
Myth is a story of a nation that contains an interpretation of the origin of the universe. Myth gives its own color to its supporting community, so it displays a unique pattern of action and contains its own special characteristics. Myths are often displayed with mystical wrapping, so they tend to be on the metaphysical side. So then it causes supporters of myths to be claimed to be conservative and dogmatic. Although in fact, this is a view that only rests on one perspective. The variety of myths circulating in the community shows that there are a variety of values that the ancient scholars wanted to inherit. However, there are positive values that still need to be explored through contemplation in order to bring out the reality side. The positive values contained in myths are: a) myths act as educational facilities, b) myths serve as a medium for conservation of natural resources, and c) myths play roles as a stimulus for the creativity of new thinking. All of these positive values aim to prosper human life and make human beings humane.Keywords : Contemplation, Myth and Reality